COVID-19 vaccination in the mass vaccination center: clinical practice and effectiveness analysis - Fan, Jie; Zhu, Ling; Wu, Xiaohua; Luo, Chunyu; Huang, Ailong; Wang, Wei (Frontiers in Public Health, 2023)
Objectives Mass vaccination campaigns can rapidly increase the vaccination rate for the COVID-19 vaccine, the establishment of mass vaccination centers is indispensable. At the beginning of March 2021, China began to carry out COVID-19 vaccination activities nationwide. Here, we aimed to evaluate the criteria established by mass vaccination centers, COVID-19 vaccination experience, the incidence of adverse events following immunization and opinions. Methods We describe the layout and functioning of Nan’an District mass vaccination center, the working mechanism, experience and effectiveness. Distribution of COVID-19 vaccine vaccination and adverse events following immunization reported in the mass vaccination center of Nan’an District were evaluated. Results From March 26, 2021 to April 28, 2022, the mass vaccination center has inoculated about 381,364 doses of COVID-19 vaccine to the population. The study found that the incidence of adverse events following immunization (AEFI) was very low (1.04/100000). The chances of having AEFI were significantly higher in COVID-19 vaccine (CHO cell) than COVID-19 vaccine (Vero cell). Conclusion The mass vaccination center was running successfully. It was effective and safe, providing vaccination services and increasing COVID-19 vaccination rates among the population. The experience of the mass vaccination center for COVID-19 in China can provide a reference for other countries and regions to carry out COVID-19 vaccination.